A REVIEW OF DEEP EUTECTIC SOLVENTS IN GREEN EXTRACTION OF CHITOSAN: COMPOSITION, EFFICIENCY, AND RECYCLABILITY - Kanani, Nufus; Wardalia, Wardalia; Kustiningsih, Indar; Adiwibowo, Muhammad Triyogo; Rusdi, Rusdi; Hartono, Rudi; Heriyanto, Heri (JURNAL INTEGRASI PROSES, 2025)
Chitosan, a biopolymer derived from chitin-rich biomass such as crustacean shells, has garnered attention for its biodegradability, biocompatibility, and wide-ranging applications. However, conventional chemical extraction methods relying on strong acids and bases pose significant environmental and safety concerns, often leading to molecular degradation and low product quality. This study explores the use of deep eutectic solvents (DESs) as a green alternative for chitosan extraction. DESs, formed from combinations of hydrogen bond donors and acceptors, offer tunable properties, lower toxicity, and recyclability. The article highlights the structural advantages, extraction efficiency, and environmental benefits of DESs over conventional methods. It also examines the integration of process intensification technologies, such as microwave and ultrasound-assisted extraction, to enhance yield and reduce energy consumption. The findings underscore DESs’ potential to produce high-purity chitosan while supporting sustainability goals and industrial scalability, offering a viable pathway toward eco-friendly biopolymer processing.